Betel (Piper betle L.) Leaf Ethanolic Extract Dechlorophyllized by Sedimentation: Uses in Conjunction with Cold Plasma and for Preparation of Active Packaging to Extend the Shelf-Life of Nile Tilapia Slices - Tagrida, Mohamed (Prince of Songkla University, 2023)
Doctor of Philosophy (Food Science and Technology), 2022